Transcending time and space: trauma narration in the Harmony Silk Factory - Hou, Xia; Omar, Noritah; Kaur, Hardev; Bahar, Ida Baizura; Fan, Yingying (https://doi.org/10.47836/jlc.9.1.02, 2022)
Tash Aw is the first renowned Malaysian writer who has brought Malaysian literature to the platform of the world. This paper uses the text, The Harmony Silk Factory(2005), by Tash Aw to investigate the relationships between traumatic memory and temporal-spatial narratives. The text utilises three narrators to tell the story of central silent character Johnny Lim, intermixing with their personal memories. We hypothesises that traumatic memories are correspondent to or characterised with special time and space arrangement of narratives. The article also frames its arguments according to the ideas proposed by Michael Toolan and Cathy Caruth, Toolan’s viewpoints about time and space in discourse and story; Caruth’s views on features of trauma. The frame of argument presupposed that circular temporal-spatial narratives have more similarities to traumatic memories than previously assumed. By analysing Jasper’s and Peter’s telling of Johnny’s experiences, the study strives to deepen the idea of chronotope arrangement being conducive to expression of traumas. The study concludes that traumas determine special arrangement of narratives, especially in the dimension of time and space, in turn, temporal-spatial narratives are to express traumas’ characteristics and even achieve some universal theme in literary works. The implication of the study allows us to view traumatic texts more objectively and deeply.